Neoglacial glaciations around Hans Tausen Iskappe, Peary Land, North Greenland - Weidick, Anker (Meddelelser om Grønland. Geoscience, 2001)
All present glacier units in central Peary Land, North Greenland, have been systematically indexed in order to register existing documentation on glacier changes. The basis for this inventory work Is the series of wide angle vertical aerial photographs flown in 1978 for Kort- og Matrikelstyrelsen. Determination of the glaciation limit on this base indicates a rise from 200 m a.s.l. at the outer coast of the Arctic Ocean to between 900 and >1000 m a.s.l. in the central areas of Peary Land. This trend is related to relatively higher precipitation and lower summer temperature at the outer coast compared to further inland. The present glacier activity of individual glacier units has been investigated by study of all available aerial photographs from the years of 1950, 1960-63 and 1978. Locally photographic documentation can be extended back to 1938. In general, the glacier changes in this century have been very small, and significant changes are restricted to outlets of the Inland Ice, and to a minor degree outlets of local glaciers with mainly western and northern aspect. Semi-permanent ice cover in the fjords leads to formation and retention of extensive floating lobes of glacier fronts. The climate of the 20th century appears to have been characterised by borderline conditions between periods of ice-free fjords and those of semi-permanent ice cover. Neoglacial maximum is generally referred to A.D. 1900, with major thinning (downwasting) and recession in the first half of the 20th century, followed by slower recession, stand-still or even readvances during the last half of the century.